PERAN GURU BIMBINGAN DAN KONSELING DALAM PENGEMBANGAN BAKAT SISWA SMA NEGERI 2 SEKAMPUNG - Hardiansyah, Fadhil; Aisyah Nur Awalin, Siti; Rahmayanty, Dinny (CONS-IEDU: Jurnal Program Studi Bimbingan Dan Konseling Islam, 2024)
Guidance and counseling is a process of providing assistance from the guidance and counseling teacher to students or students in an effort to solve all the problems faced by students or students, not only students who come to provide counseling guidance in problematic situations but also come of their own free will to provide guidance and counseling. counseling.This research aims to determine the role of guidance and counseling teachers in developing the talents of students at State High School 2 Sekampung, East Lampung Regency. This type of research is field research, with the nature of qualitative descriptive research. This research uses interview, observation and documentation data collection techniques. Interviews were conducted with resource persons, namely BK teachers, class X students at State High School 2 Sekampung, and parents. The data was analyzed deductively.Based on the research results, guidance and counseling teachers have played a role in developing the talents of students at State High School 2 Sekampung, East Lampung Regency, namely as mentors and as information providers whose job is to provide material using classical services, individual services, and distribution and placement services. Guidance and guidance teachers as counselors maximize clasical services so that students who do not routinely receive individual guidance are still given guidance and counseling using classical services carried out in the classroom